Physicochemical Analysis of Water Quality of Brook Kuruçay - Mutlu, Ekrem; Uncumusaoğlu, Arzu Aydın (Turkish Science and Technology Publishing (TURSTEP), 2016)
In this study, through the analyses of water samples taken from 9 stations on the brook between July 2012 and June 2013, we aimed to determine the monthly and seasonal changes in water quality parameters of Brook Kuruçay, to determine the water quality properties, to reveal the pollution problems, to determine the suitability level in terms of aquatic life and to classify the quality of water in accordance with Surface Water Quality Management Regulation’s Inland Surface Water Classes criteria. The study area is located southeast of the Hafik District of Sivas city and the altitude is 2608 m. The water samples were collected from 9 stations established on the brook, and some physicochemical parameters and heavy metal concentrations were analyzed in water samples. The cleaning and maintenance of all of the equipment, land-type measurement tools, and glass sampling containers to be used in sampling were made 1 day before sampling. Sampling tubes were immersed into 15 cm below the water surface for taking water samples. Heavy metal concentrations were determined in the Sivas Provincial Control Laboratory in the same day with sampling (within 5 hours). The total alkalinity, total hardness, ammonium nitrogen, nitrite, nitrate, ammonium azote, phosphate, sulfite, sulfate, chloride, sodium, potassium, suspended solid matter (SSM), chemical oxygen demand (COD), biological oxygen demand (BOD), calcium, magnesium, ferrous, lead, copper, zinc, nickel, mercury and cadmium analyses of water samples were performed.
As a result of the analyses, it was determined that, since Brook Kuruçay falls into the water resource class, which is the most sensitive to pollution, the water quality of the brook should be monitored regularly.
Keywords: S; Agriculture (General); Water Pollution; Surface water; Agriculture; S1-972; Surface Water; Hafik; Water Quality; Brook Kuruçay; 6. Clean water; 11. Sustainability